Hotair mediates tumorigenesis through recruiting EZH2 in colorectal cancer - Huang, Kai‐bin; Zhang, Shi‐pai; Zhu, Yong‐jun; Guo, Chun‐hua; Yang, Min; Liu, Jun; Xia, Li‐gang; Zhang, Jin‐fang (Journal of cellular biochemistry, 2019)
Long noncoding RNAs (lncRNA)  have been demonstrated to extensively participate in a wide spectrum of biological activities ranging from embryogenesis and cancer progression. HOX transcript antisense RNA (Hotair), an lncRNA located in the HOXC locus, has been reported to play an important role in carcinogenesis. As a well‐known oncogene, it potentiates cancer metastasis and tumor progression. And it also serves as a biomarker for poor prognosis and tumor recurrence. In this study, Hotair was found to be upregulated in colorectal cancer (CRC) cells and clinical specimens. Further investigation showed that knockdown of Hotair dramatically suppressed cell proliferation and colony formation, suggesting that Hotair may stimulate tumorigenesis of CRC. The enhancer of zeste homolog 2 (EZH2), a regulator of epigenetic modification, was upregulated in CRC cells and clinical samples. And the silence of EZH2 significantly suppressed cell viability and colony formation. Furthermore, the RNA immunoprecipitation assay revealed that Hotair directly bound EZH2 in CRC cells. In conclusion, Hotair mediated tumorigenesis via recruiting EZH2, which might shed light on the development of a novel therapeutic approach for patients with CRC. Hotair mediated tumorigenesis via recruiting EZH2, which might shed light on the development of a novel therapeutic approach for patients with colorectal cancer (CRC).